MODEL PENGELOLAAN SUMBERDAYA WILAYAH PESISIR PROVINSI KALIMANTAN UTARA BERBASIS MASYARAKAT DAN BERKELANJUTAN - Basri (Lex Journal: Kajian Hukum & Keadilan, 2021)
What is very important in the sustainable management of coastal marine areas is the involvement of local communities from planning to implementation. This study aims to explain that community-based and sustainable management of coastal marine areas in North Kalimantan is the most ideal coastal management model. This type of research is the normative legal research method with qualitative analysis. The results showed the benefits of community-based and sustainable management of the coastal marine area of ​​North Kalimantan in improving the welfare of coastal communities because it is based on the potential and characteristics of the coastal marine area. Thus, community-based and sustainable management of the coastal marine area of ​​North Kalimantan is a model of coastal area management that favors coastal communities. Keywords; Coastal areas, Indigenous based, sustainable